Compositional and Functional Analysis of the Microbiome in Tissue and Saliva of Oral Squamous Cell Carcinoma - Zhang, Zhen; Yang, Junjie; Feng, Qiang; Chen, Bin; Li, Meihui; Liang, Cheng; Li, Mingyu; Li, Zhihui; Xu, Qin; Zhang, Lei; Chen, Wantao (Frontiers in Microbiology, 2019)
Oral squamous cell carcinoma (OSCC) is affected by the interaction between oral pathogen and holobionts, or the combination of the host and its microbial communities. Studies have indicated the structure and feature of the microbiome in OSCC tissue and saliva, the relationships between microbial flora and OSCC sites, stages remain unclear. In the present study, OSCC tissue (T), saliva (S) and mouthwash (W) samples were collected from the same subjects, and carried out the microbiome study by 16S sequencing. The results showed the T group was significantly different from the S and W groups with the character of lower richness and diversity. Proteobacteria were most enriched in the T group at the phylum level, while Firmicutes were predominant in groups S and W. At the genus level, the predominant taxa of group T were Acinetobacter and Fusobacterium, and for group S and W, the predominant taxa were Streptococcus and Prevotella. The genera related to late stage tumours were Acinetobacter and Fusobacterium, suggesting microbiota may be implicated in OSCC developing. Both compositional and functional analyses indicated that microbes in tumour tissue were potential risk factors for the initiation and development of OSCC.